Prevalence and diversity of Babesia spp. in questing Ixodes ricinus ticks from Norway - Øines Øivind; Radzijevskaja Jana; Paulauskas Algimantas; Rosef Olav (Parasites & Vectors, 2012)
Abstract Background Ixodes ricinus ticks transmit Babesia species to vertebrate hosts. Using molecular tools we were able to detect the presence of this piroplasmid in its vector. The aims of this study were to investigate the prevalence and identity of Babesia species in questing ticks collected in various areas of Norway. Methods DNA from questing l. ricinus ticks were examined with a realtime PCR for the presence of Babesia. Positive samples of tick DNA were identified to species using PCR, and sequence analysis. Results From a total of 1908 questing l. ricinus ticks, 17 (0.9%) indicated the presence of Babesia spp. after realtime-PCR screening. Ixodes ricinus harbouring Babesia spp. was detected in 9 out of 22 localities. Further molecular analyses of DNA from these positive ticks indicate the presence of Babesia venatorum, B. divergens, B. capreoli and a currently undescribed Babesia in Norwegian ticks. The most prevalent was B. venatorum found in 71% of the positive ticks. Conclusions A total of 17 out of 1908 (0.9%) ticks were positive for Babesia. Our data confirm that there are several Babesia species in ticks in Norway. Babesia venatorum was the most prevalent. This species has a zoonotic potential and may cause human babesiosis following a tick bite.